2017
DOI: 10.1080/20445911.2017.1282489
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between language switching experience and executive functions in bilinguals: an Internet-based study

Abstract: We examined the relationship between self-reported everyday language switching experience and the performance of early bilinguals in tasks measuring different executive functions. Our participants were Finnish-Swedish early bilinguals, aged 16-41 years (N = 66, Experiment 1) and 18-69 years (N = 111, Experiment 2). An earlier study using a sample from a similar population discovered a negative relationship between self-reported language switching and a mixing cost in error rates in a number-letter task. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 53 publications
4
43
2
Order By: Relevance
“…This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/ 27 bilingual language and executive control. These novel findings corroborate recent behavioral investigations showing that the social diversity of language use impacts performance on domain general executive control tasks, including language and task switching (Hartanto & Yang, 2016;Hofweber, Marinis, & Treffers-Daller, 2016;Jylkkä et al, 2017;Soveri, Rodriguez-Fornells, & Laine, 2011;Verreyt et al, 2016;see also, Prior & Gollan, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/ 27 bilingual language and executive control. These novel findings corroborate recent behavioral investigations showing that the social diversity of language use impacts performance on domain general executive control tasks, including language and task switching (Hartanto & Yang, 2016;Hofweber, Marinis, & Treffers-Daller, 2016;Jylkkä et al, 2017;Soveri, Rodriguez-Fornells, & Laine, 2011;Verreyt et al, 2016;see also, Prior & Gollan, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…One proposed mechanism for this Bilingual Training has been language switching (Linck et al, 2012;Rodriguez-Fornells et al, 2006). Earlier studies examining the relationship between language switching frequency and EF have, however, yielded inconsistent results (Hartanto & Yang, 2016;Johnson et al, 2015;Jylkkä et al, 2017;Paap et al, 2017;Prior & Gollan, 2011;Soveri et al, 2011;Verreyt et al, 2016). This discrepancy between previous studies suggests that the methods for assessing language switching and EF may be problematic, or that language switching does not train EF.…”
Section: Discussionmentioning
confidence: 99%
“…On a related note, Soveri and colleagues (2011) found that a higher frequency of bilingual every-day language switching was related to a smaller mixing (but not switching) cost in errors on a number-letter switching task. Soveri and colleagues suggested that mixing cost reflects top-down management of two competing tasks, and thus closely resembles an everyday conversation in which a bilingual must decide which language to use by recruiting sustained control and general monitoring processes (although note that this finding was not replicated in a similar follow-up study from the same group; Jylkkä et al, 2017). …”
Section: Discussionmentioning
confidence: 99%